Nosocomial Bloodstream Infections in Children in Intensive Care Unit: Organisms, Sources, Their Sensitivity Pattern and Outcome of Treatment - Tauhid, Syed Ahsan; Chowdhury, MAK Azad; Hoque, Md Mahbubul; Kamal, MA; Haque, Emdadul (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Background: Nosocomial bloodstream infection in paediatric ICU is a leading, preventable infectious complication in critically ill patients and has a negative impact on patients outcome. This study was done to determine the type of pathogens responsible for nosocomial infections and its sensitivity pattern, to evaluate the probable sources (fomites) of nosocomial infections and also to compare the outcome of treatment between children with and without nosocomial bloodstream infections in terms of length of ICU stay and mortality Material and methods: This study was conducted in the intensive care unit of Dhaka Shishu(children) hospital. Children between 0-5 years of age were included in the study. Blood culture positive case at the time of admission and Children discharged or died within 48 hours of admission were excluded. When children clinically suspected to have nosocomial infections, their blood culture and swab culture of probable sources were done. Results: Out 110 patients, 23(20.9%) patients developed nosocomial BSI. Neonates were found to be more susceptible to develop nosocomial BSI. Most of the organisms (86%) were Gram negative bacilli. Klebsiella was the most common pathogens (30.78%) followed by acinatobacter (21.73%), E-coli (13.04%), Pseudomonas (8.7%). Type of micro-organisms and their sensitivity pattern obtained from blood culture and sources culture of corresponding patient were almost similar which indicate the clue for probable source of nosocomial infection. Microorganisms were almost sensitive to Imipenem but there were high resistance to commonly used antibiotics including third generation cephalosporins. ICU acquired infections increase hospital mortality and duration of hospital stay. Conclusion: Nosocomial bloodstream infections in children in ICU are associated with high mortality rate and prolong hospital stay. Neonates are more susceptible to develop nosocomial BSI than children aged above 28 days. Gram negative organisms are predominant isolates and are developing resistance to commonly used antibiotics including third generation cephalosporin. Imipenem is the most effective and reliable antibiotic option. Fomites especially health care device including IV canula, suction catheter, endotracheal tubes, oxygen mask are the important probable sources of nosocomial infections. J Bangladesh Coll Phys Surg 2017; 35(3): 115-122